How to change for loop to parfor loop?
8 views (last 30 days)
Show older comments
Is it possible to execute the following code using parfor loop?
for ii = 1 : 1 : N
x_ref = X(ii); y_ref = Y(ii);
nghlst_Local = nghlst(ii, find(nghlst(ii, :))); Nl = length(nghlst_Local);
x_Local = X(nghlst_Local, 1); y_Local = Y(nghlst_Local, 1);
Phi = ones(Nl+1, Nl+1); Phi(end, end) = 0;
Bx = zeros(Nl+1,1); By = zeros(Nl+1,1); Bxx = zeros(Nl+1,1); Byy = zeros(Nl+1,1);
for jj = 1 : 1 : Nl
for kk = 1 : 1 : Nl
rx = x_Local(jj,1) - x_Local(kk,1);
ry = y_Local(jj,1) - y_Local(kk,1);
Phi(jj, kk) = 1 / sqrt( rx^2 + ry^2 + c^2);
clear rx ry
end
rx = x_ref - x_Local(jj);
ry = y_ref - y_Local(jj);
Bx(jj, 1) = -rx/(rx^2 + ry^2 + c^2)^(3/2);
end
invPhi = inv(Phi);
CX = Bx' * invPhi; CX = CX (1, 1:end-1); Wx (ii, nghlst_Local) = CX;
end
I know nested parfor loops generally give no computational benefits. So, which for loop should I change?
0 Comments
Answers (0)
See Also
Categories
Find more on Loops and Conditional Statements in Help Center and File Exchange
Products
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!